2011
DOI: 10.1038/modpathol.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cathepsin K in neoplasms harboring TFE3 gene fusions

Abstract: Cathepsin K is a protease whose expression is driven by microphthalmia transcription factor (MITF) in osteoclasts. TFE3 and TFEB are members of the same transcription factor subfamily as MITF and all three have overlapping transcriptional targets. We have shown that all t(6;11) renal cell carcinomas, which harbor an Alpha-TFEB gene fusion, as well as a subset of the Xp11 translocation renal carcinomas, which harbor various TFE3 gene fusions, express cathepsin K, while no other common renal carcinoma does. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 24 publications
5
79
0
1
Order By: Relevance
“…Along these lines, we previously noted that the ASPSCR1-TFE3 renal cell carcinomas tend to have higher nuclear grade and more voluminous cytoplasm than the PRCC-TFE3 renal cell carcinomas. 3,4 A further more objective difference between these neoplasms is their differential immunohistochemical expression of the cysteine protease cathepsin K. 50,51 We have previously shown that a majority (12 of 14, or 86%) of PRCC-TFE3 renal cell carcinomas diffusely express cathepsin K, whereas all eight ASPSCR1-TFE3 renal cell carcinomas tested have been negative for this immunohistochemical marker. As cathepsin K expression is typically driven by the transcription factor MITF, which is in the same family as TFE3 and TFEB, and has overlapping activity, our hypothesis has been that the PRCC-TFE3 fusion protein is better able to activate cathepsin K expression compared with the ASPSCR1-TFE3 fusion protein.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, we previously noted that the ASPSCR1-TFE3 renal cell carcinomas tend to have higher nuclear grade and more voluminous cytoplasm than the PRCC-TFE3 renal cell carcinomas. 3,4 A further more objective difference between these neoplasms is their differential immunohistochemical expression of the cysteine protease cathepsin K. 50,51 We have previously shown that a majority (12 of 14, or 86%) of PRCC-TFE3 renal cell carcinomas diffusely express cathepsin K, whereas all eight ASPSCR1-TFE3 renal cell carcinomas tested have been negative for this immunohistochemical marker. As cathepsin K expression is typically driven by the transcription factor MITF, which is in the same family as TFE3 and TFEB, and has overlapping activity, our hypothesis has been that the PRCC-TFE3 fusion protein is better able to activate cathepsin K expression compared with the ASPSCR1-TFE3 fusion protein.…”
Section: Discussionmentioning
confidence: 99%
“…18 Cathepsin K is a protease whose expression is driven by microphthalmia transcription factor (MITF) in osteoclasts. 19 Cathepsin K is consistently and diffusely positive in ASPS (Figure 4). 19 Although these 2 immunohistochemical stains are highly sensitive, they are not entirely specific because other tumors also show positivity (described below).…”
Section: Microscopic Featuresmentioning
confidence: 99%
“…19 Cathepsin K is consistently and diffusely positive in ASPS (Figure 4). 19 Although these 2 immunohistochemical stains are highly sensitive, they are not entirely specific because other tumors also show positivity (described below). Often, ASPS is positive for desmin and muscle-specific actin.…”
Section: Microscopic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…ASPSCR1-TFE3), in contrast to the absence of staining in the conventional clear cell, papillary, chromophobe RCCs or oncocytomas, or in any adjacent nonneoplastic renal tissue. 11,12 Outcome data on this entity are still relatively premature and highly variable, with some patients having an extremely aggressive course and others a relatively indolent one. Overall, survival is similar to that seen in patients with clear cell RCC, and among patients with PRCC-TFE3 RCC and ASPSCR1-TFE3 RCC, only advanced stage and older age at diagnosis independently predicted death in a multivariate analysis of the 2 tumors.…”
Section: Xp11 Translocation-associated Renal Cellmentioning
confidence: 99%